Arquitectura simbiótica: propuesta edificio de vivienda con centro de reciclaje (Bello, Antioquia) - López Montoya, César Rodrigo (Universidad Antonio Nariño, 2021)
The concern for solid waste generated in the urban centers of the Aburrá Valley, the meaning of hygienic and sanitary type, the problem begins from the moment in the community places the waste in the public road so that someone withdraws but does not know correct form and the suitable places of its final disposition; Therefore, there is a need to create a collection system, as a fundamental part of a public service, that integrates the inhabitants of the sector, educating them so that they have better tools when it comes to organizing, classifying and recycling in a more effective way, in order to avoid contamination of the public streets and water tributaries. The planning process of solid waste management at the metropolitan area level is of great relevance to improve the current problems. Therefore, it is essential that basic guidelines are established so that this level can advance the formulation and execution of the Municipal and Architectural plans, in a way that allows the administration of the diverse solid waste flows, according to local conditions so that they in turn generate culture in each of their inhabitants.Through the sustainable and hybrid design between collective housing and a recycling center, allow the correct symbiosis of the habitat in relation to the disposal of waste generated in the industrial, residential and commercial sector of Bello - Antioquia. The proposal proposes to create a system of hybrid housing with a waste management plant, which balances the effective infrastructural link in the management of waste in its immediate environment. At the same time create collective spaces based on the recycling of solid waste in strategic points, not only for collection but also for dissemination, education and example for the community, a constant search for awareness and integration.